2020
DOI: 10.3389/fphys.2020.00923
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration of Irisin and Brain-Derived-Neurotrophic Factor and Their Association With the Level of Erythrocyte Adenine Nucleotides in Response to Long-Term Endurance Training at Rest and After a Single Bout of Exercise

Abstract: The study aimed to assess the effect of a single bout of incremental exercise on irisin and BDNF plasma concentrations as related to erythrocyte purine nucleotides concentration at rest and after exercise. Master endurance master athletes (training experience 38 ± 6 years) and a group of untrained participants completed a single bout of progressive incremental exercise test until exhaustion. The dual-energy x-ray absorptiometry and blood collection were performed. Blood was taken twice at rest and 10 min after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…In literature, a previous study has failed to detect any changes in irisin expression after an acute bout of exhausting exercise. 14 Only some authors documented modest changes of irisin levels immediately following (0-10 min) an acute bout of incremental exercise, 9 , 11-13 failing to detect post-exercise changes (after 60 and 180 min). 12 , 13 Moreover, a meta-analysis has stated that irisin increased within 15 min, following an acute exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, a previous study has failed to detect any changes in irisin expression after an acute bout of exhausting exercise. 14 Only some authors documented modest changes of irisin levels immediately following (0-10 min) an acute bout of incremental exercise, 9 , 11-13 failing to detect post-exercise changes (after 60 and 180 min). 12 , 13 Moreover, a meta-analysis has stated that irisin increased within 15 min, following an acute exercise.…”
Section: Discussionmentioning
confidence: 99%
“… 7 There seem to be a dose-response relationship between exercise and irisin elevation, 9 , 10 but contradictory results have been reported considering research that evaluate the irisin response to an incremental exercise until exhaustion. In particular, acute responses immediately (0-15 minutes) after a maximal incremental exercise test have shown either a slight rise 9 , 11-13 or no effects 14 on serum or plasma irisin levels, while the studies that have measured the amount of circulating irisin at least 30 min following an incremental exercise to exhaustion did not find significant changes in the myokine concentration. 12 , 13 The existing research seem to suggest that the elevation of irisin following an incremental exercise test to exhaustion is transient, and it is likely that after 24 hours the levels have returned to baseline conditions.…”
mentioning
confidence: 99%
“…Erythrocytes were washed with buffered 0.9% NaCl solution and centrifuged (1,000 × g , 5 min, 4°C). The nucleotide concentration was determined in washed erythrocytes and expressed in relation to the volume of erythrocytes as previously described ( Pospieszna et al, 2019 ; Rodziewicz et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, the results of a meta-analysis covering 12 studies in 8 articles reported that chronic resistance training unexpectedly and significantly reduced circulating concentrations of irisin in a randomized controlled trial and that irisin also tended to be reduced in endurance exercise (Qiu et al, 2015). In a study conducted by Rodziewicz et al (2020), the effects of a single incremental exercise on the plasma concentrations of irisin and BDNF were evaluated in subjects applying a treadmill for maximal fitness testing. While the study found a significant positive correlation between irisin concentrations and fasting glucose and insulin, no significant effect of irisin by exercise was observed (Rodziewicz et al, 2020).…”
Section: E Ects Of DI Erent Types Of Exercise On Irisinmentioning
confidence: 99%
“…In a study conducted by Rodziewicz et al (2020), the effects of a single incremental exercise on the plasma concentrations of irisin and BDNF were evaluated in subjects applying a treadmill for maximal fitness testing. While the study found a significant positive correlation between irisin concentrations and fasting glucose and insulin, no significant effect of irisin by exercise was observed (Rodziewicz et al, 2020). A recent systematic review and meta-analysis in 2021 compared the effect of exercise on irisin blood levels in 33 studies (Briken et al, 2016), with increased levels of irisin in 23 of these studies and decreased in another 10, with rather inconsistent results in individual studies.…”
Section: E Ects Of DI Erent Types Of Exercise On Irisinmentioning
confidence: 99%